The crucial evaluation indexes and relative measurement methods of edible value for fresh fruits and vegetables: A review - Yiqin Zhang; Hongxuan Wang; Hangjun Chen; Ruiling Liu; Huizhi Chen; Xiangjun Fang; Jianbo Xiao; Weijie Wu; Haiyan Gao (Future Postharvest and Food)
Abstract Fresh fruits and vegetables (F&V), with their attractive sensory, flavors, and nutrients, occupy a highly valuable part of people's daily diet. Plenty of postharvest studies have focused on the effects of preservation techniques on the edible quality and nutrients of F&V. Therefore, it is crucial to summarize the research methods of those quality and nutritional indicators for F&V. This work reviews the measurement and analysis methods on these parameters of postharvest F&V which have been validated by numerous publications, including firmness, sugars/acids, pigments, phenols, etc. Importantly, some instruments are involved in these experimental methods, such as firmness tester, spectrophotometer, gas chromatograph, and so on. Furthermore, some promising analysis methods in the past decades combined with advanced technologies are also raised in our discussion. This work is expected to provide guidance and normative significance for future research on quality assessment, preservation, and processing characteristics of F&V.